Coagulation, anticoagulation and fibrinolytic system of blood in patients with acute ischemic heart disease and features of changes in combination with diabetes mellitus (cohort prospective study) - Karpenko, Olena (ScienceRise: Medical Science, 2019)
Aim. To evaluate the clotting, anticoagulant and fibrinolytic activity of blood in patients with acute coronary heart disease (ACHD) and to determine the peculiarities of changes when combined with ACHD and DM2. Materials and methods. 60 persons were diagnosed MI with ST-segment elevation, MI without ST-segment elevation, unstable angina. Among them: 30 patients with ACHD (Group I), 30 patients with ACHD in combination with DM2 (Group II) and 15 practically healthy subjects (control group). The average age of the patients is 64.2±10.01 years, the number of men is 30 (50 %), and women – 30 (50%). Patients were diagnosed with hemostatic parameters in venous blood. Results. With a general similarity of changes in the anticoagulant system in both groups, attention was drawn to the significant exacerbation of antithrombin activity in patients in group II, which was accompanied by oppression of the PtC system. Thus, the content of ATIII in this group was lower than the control group by 27.8 % (65.5 [54.0; 76.0], p <0.001), and PtC decreased by 37.2 % (0.66 [0, 6, 0,7], p <0,001), whereas in patients of group I anticoagulant activity decreased only at the expense of ATIII-78,0 [74,0; 82.0] versus 90.0 [80.0; 110,0], p<0,01), while the level of PtC did not undergo significant changes. The indicated changes took place against the suppression of fibrinolytic activity in the two groups under study. At the same time, XIIa fibrinolysis appeared to be the most prolonged in group II, namely, 1.6 times in comparison with the same indicator in group І (20.4 [18.5; 23.7] vs. 13.05 [12.6; 13, 7], p<0.001) and 2.6 times different from control (8.0 [7.0; 11.0]; p<0.001). Conclusions. Changes detected as a result of studying the coagulation linkage of hemostasis in the study groups indicate acceleration of blood coagulation at all stages of coagulation. The presence of DM2 is characterized by a number of changes from the system of hemostasis, which determine the increased risk of thrombotic complications